Short-term air temperature forecasting using Nonparametric Functional Data Analysis and SARMA models. (January 2019) - Curceac, Stelian; Ternynck, Camille; Ouarda, Taha B.M.J.; Chebana, Fateh; Niang, Sophie Dabo
Abstract: Air temperature is a significant meteorological variable that affects social activities and economic sectors. In this paper, a non-parametric and a parametric approach are used to forecast hourly air temperature up to 24 h in advance. The former is a regression model in the Functional Data Analysis framework. The nonlinear regression operator is estimated using a kernel function. The smoothing parameter is obtained by a cross-validation procedure and used for the selection of the optimal number of closest curves. The other method applied is a Seasonal Autoregressive Moving Average (SARMA) model, the order of which is determined by the Bayesian Information Criterion. The obtained forecasts are combined using weights calculated based on the forecast errors. The results show that SARMA has a better performance for the first 6 forecasted hours, after which the Non-Parametric Functional Data Analysis (NPFDA) model provides superior results. Forecast pooling improves the accuracy of the forecasts. Highlights: Functional Data Analysis and autoregressive models were used to forecast hourly air temperature up to one day in advance. The AR model has a better performance for the first 6 forecasted hours and FDA is superior for horizons of 7 to 24 hours. Both models showed consistently good results from May until November and inferior performance in February and March. Linear combination of the forecasts from the two models improves the accuracy.